TINDAK PIDANA MENYEBARKAN INFORMASI YANG MENIMBULKAN RASA KEBENCIAN KEPADA SUKU BATAK - Aprilia Manurung; Yohannes Saputra Banurea; Herman Brahmana (The Juris, 2021)
SARA is a very sensitive matter among individuals or community groups, which can lead to conflicts that lead to divisions, especially in Indonesia related to the SARA conflict. This study uses a normative juridical research based on the main legal material, namely the principles of law related to law. And the nature of the research uses descriptive analysis, in which this research aims to analyze the elements of the perpetrators of criminal acts who spread false information so as to cause a sense of hatred towards the Batak tribe, whether it is committed against certain individuals or groups. Public. The legal policy for the perpetrators of information dissemination that causes hatred to the Batak tribe is a legal fact and the elements contained in article 28 paragraph (2) about how a person / defendant has committed a crime deliberately which can cause feelings of hatred. In this case the defendant found guilty and committed the crime of spreading false information on social media.